Irrigation with saline water in the cultivation of mini watermelon under phosphate fertilization - G. S. Lima; S. S. Silva; L. A. A. Soares; A. A. R. Silva; H. R. Gheyi; R. G. Nobre; W. B. B. Souza; S. T. A. Silva; M. A. Guedes; V. K. N. Oliveira (Brazilian Journal of Biology, 2023)
Abstract The objective of this study was to evaluate the water status, photosynthetic pigments, and photochemical efficiency of mini watermelon plants under salt stress and phosphate fertilization. The experiment was conducted in pots under greenhouse conditions in Pombal, PB, Brazil. The experimental design used was randomized blocks in a 5 × 4 factorial scheme, with five levels of electrical conductivity of irrigation water - ECw (0.3, 1.3, 2.3, 3.3, and 4.3 dS m-1) and four doses of phosphorus (60, 80, 100, and 120% of the recommendation), with three replicates. The relative water content in the tissues decreased with the increase in ECw levels in all phosphorus doses, with decreases of 7.05, 7.81 and 8.83% per unit increase in ECw, in plants fertilized with 80, 100 and 120% P2O5. On the other hand, ECw levels increased electrolyte leakage, regardless of phosphorus doses of the recommendation. The synthesis of photosynthetic pigments and the quantum efficiency of photosystem II were inhibited by increasing water salinity from 0.3 dS m-1 in plants grown under phosphorus doses above 60% of the recommendation. Water salinity from 0.3 dS m-1 reduced chlorophyll b contents, initial, maximum, and variable fluorescence of mini watermelon plants, with a decrease of 11.86, 4.51, 4.53, and 4.54% per unit increment of ECw, respectively.